The Effect of Physical Attractiveness and Gender Counselors on Students Self Disclosure (Universitas Negeri Semarang, 2019)
The purpose of this study was to examine the effect of physical attractiveness and gender on self disclosure. This study has two independent variables and one dependent variable. The subjects in this study were students of SMAN 12 Semarang then 118 students were taken as research subjects. The data analysis technique used was 2-way ANAVA test and average difference. The results showed that the physical attractiveness and gender counselor had an influence on self disclosure. And, the counselors interested and female counselors are preferred more. This research proved that there was an interaction between physical attractiveness and gender with self disclosure for students in Semarang City, Indonesia.